Tec-kinase-mediated phosphorylation of fibroblast growth factor 2 is essential for unconventional secretion - Ebert, Antje; Laußmann, Mareike; Wegehingel, Sabine; Kaderali, Lars; Erfle, Holger; Reichert, Jürgen; Lechner, Johannes; Beer, Hans-Dietmar; Pepperkok, Rainer; Nickel, Walter (Traffic, 2010)
Fibroblast growth factor 2 (FGF2) is a potent mitogen that is exported from cells by an endoplasmic reticulum (ER)/Golgi-independent mechanism. Unconventional secretion of FGF2 occurs by direct translocation across plasma membranes, a process that depends on the phosphoinositide phosphatidylinositol 4,5-biphosphate (PI(4,5)P2) at the inner leaflet as well as heparan sulfate proteoglycans at the outer leaflet of plasma membranes; however, additional core and regulatory components of the FGF2 export machinery have remained elusive. Here, using a highly effective RNAi screening approach, we discovered Tec kinase as a novel factor involved in unconventional secretion of FGF2. Tec kinase does not affect FGF2 secretion by an indirect mechanism, but rather forms a heterodimeric complex with FGF2 resulting in phosphorylation of FGF2 at tyrosine 82, a post-translational modification shown to be essential for FGF2 membrane translocation to cell surfaces. Our findings suggest a crucial role for Tec kinase in regulating FGF2 secretion under various physiological conditions and, therefore, provide a new perspective for the development of a novel class of antiangiogenic drugs targeting the formation of the FGF2/Tec complex.
Gesehen am 27.02.2023